Cannabis Use and Increased 90-Day Postoperative Medical Complications Following Foot and Ankle Arthrodesis - Victoria E. Bergstein BA; Arman Kishan MBBS; Stanley E. Zhu BS; James R. Ficke MD; Amiethab A. Aiyer MD (Foot & Ankle Orthopaedics)
Category: Ankle; Midfoot/Forefoot Introduction/Purpose: As medical and recreational cannabis use continues to increase in prevalence across the United States, it is important to understand the impacts of sustained cannabis use on one’s health. Previous literature has shown the potential for cannabidiol products to aid in the improvement of some osteoarthritic symptoms. However, there is a paucity of literature examining the relationship between cannabis use and postoperative medical outcomes for end stage osteoarthritis management, including procedures such as foot and ankle arthrodesis. Therefore, the purpose of this study was to investigate the relationship between cannabis use and the incidence of medical complications within 90 days of foot or ankle arthrodesis. Methods: A retrospective review of a national insurance claims database was performed from 2010 to 2022. CPT codes were used to identify patients who underwent arthrodesis of the ankle, subtalar, talonavicular, calcaneocuboid, naviculo-cuneiform, midtarsal, tarsometatarsal, metatarsophalangeal, or interphalangeal joints. Of those patients, those with established diagnoses of cannabis use disorder, cannabis dependency, or cannabis addiction were identified using ICD-9 and -10 codes. This cannabis cohort was matched 1:4 on the basis of age, sex, and Charlson Comorbidity Index (CCI) to a control cohort without a history of cannabis use to remove potential confounding upon comparison. Demographic and comorbidity profiles, as well as medical and surgical post-operative outcomes were compared using Chi-square tests. Results: Out of 192,162 patients undergoing foot or ankle arthrodesis, 6,387 had a documented history of cannabis use. Compared to controls, the cannabis cohort was significantly younger (mean age 44.1 vs. 56.5; p< 0.001), exhibited a higher comorbidity burden (mean CCI 1.59 vs. 1.38; p< 0.001), and had a greater proportion of male patients (48.2% vs. 31.9%; p< 0.001). Post-matching for age, CCI, and sex, cannabis users demonstrated a significantly higher incidence of medical complications within 90 days of their index ankle fracture ORIF procedure. Notably, cannabis users exhibited elevated rates of various complications, including pneumonia, deep venous thrombosis, pulmonary embolism, myocardial infarction, stroke, surgical site infection, cardiac arrest, acute kidney injury, urinary tract infection, sepsis, and hypoglycemia compared to matched controls (all p< 0.001). Conclusion: Cannabis use is associated with increased incidences of many serious medical complications within 90 days of foot or ankle arthrodesis. These results may help better inform physicians and patients about the increased postoperative risks cannabis users may face, which may lead to the implementation of tailored perioperative care. Further, these results emphasize the need for further research on the molecular mechanisms of cannabis to understand the risk-benefit ratio between the therapeutic effects of cannabidiol for arthritic pain relief, and the adverse outcomes that may result following surgical intervention.